Analisis Pengendalian Persediaan Pasir Silika dengan Metode EOQ dan JIT pada PT. ABC - A. Yassir Ardani; Moh. Jufriyanto; Hidayat Hidayat (Universitas Islam Raden Rahmat, Malang, 2024)
PT. ABC is a business that operates in the cement production sector. This company often experiences silica sand raw material inventory below the minimum limit of the safety stock applicable in the company for each month, as a result of which the high frequency of orders causes the cost of ordering to swell. Therefore, an analysis of raw material inventory control must be carried out in order to determine the maximum inventory quantity. EOQ and JIT are techniques in controlling inventory that are relatively easy to minimize the total cost of inventory in the form of total storage and ordering costs. The results obtained with a need for 297,985 tons, the cost charged by the company in one year is Rp. 100,671,298. With the EOQ method, the cost is Rp. 38,236,200 or 62% more efficient. JIT method costs Rp. 15,609,863, or 85% more efficient than the company's policy.